Corporate Governance and Bank Performance: Conventional vs Islamic Banks in Malaysia - Muhammad, Mahdi Billah (2019)
Banks plays one of the vital roles in the country and economics financial hub. Therefore, it is necessary to have proper governance in this sector in order to control the monetary policy of the economy and avoid any financial crisis. The main purpose of this research is to study the effect of corporate governance variables on the profitability of conventional and Islamic banks in Malaysia. A total of 18 banks were selected for the period covering 2013 to 2017 in order to identify the firm performance by the two most popular measurement tools that are ROA and ROE. Eleven variables which include three control variables were selected in order to conduct this research. Based on the descriptive study it is found that board size and other variables of the conventional bank were much higher compared to the Islamic bank. Further, a T-test is conducted in order to find the significance among the variable and found that except ROE, independent directors, foreign directors, and average remuneration all other variables found to be significant with each other including the control variables. Further, the pooled panel regression analysis indicates that all the variables except independent directors, female directors and two control i.e. bank size and customer deposit variable found insignificant with bank performance. Finally, from subsample analysis, for conventional bank, the remuneration of directors, female directors, bank age, board size and foreign directors and for Islamic bank independent directors, female directors, board meeting, bank size, customer deposit, board size, age of directors and education qualification are consistent with the entire sample. Therefore, based on the study it is concluded that there is a relationship between corporate governance variables with bank performance.